Focusing Treatment on Pregnant Women With COVID Disease - Emanoil, Alina-Raluca; Stochino Loi, Emanuela; Feki, Anis; Ben Ali, Nordine (Frontiers in Global Women's Health, 2021)
Since the emergence of a novel coronavirus in China at the end of December 2019, its infection - COVID-19 - has been associated with high morbidity and mortality and has left healthcare systems wrestling with the optimal management strategy, especially for vulnerable populations, such as pregnant women. At this moment, few resources exist to guide the multi-disciplinary team through decisions regarding optimal maternal-foetal treatment and delivery timing. In this article, we present the drugs and vaccines under investigation as potential treatments and prevention for COVID-19 infection. Based on a comprehensive evaluation, we prioritised these possible treatments, and provide dose-response and dose-toxicity information on each drug. Currently, there is limited but very increasing reassuring information concerning vaccines to prevent SARS-CoV-2 during pregnancy, and in this review, we also emphasise the results (mostly positive) provided by the few small trials evaluating COVID-19 vaccines in pregnant patients.